2020
DOI: 10.1002/14651858.cd003229.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotonics for venous insufficiency

Abstract: Analysis 2.1. Comparison 2: Sensitivity analysis excluding studies that allowed the use of elastic stockings, Outcome 1: Oedema in the lower legs (dichotomous variable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 88 publications
0
49
0
13
Order By: Relevance
“…A Cochrane review and meta-analysis of phlebotonics for venous insufficiency, published in 2020, analyzed 56 randomized, double-blind, placebo-controlled trials involving 7690 participants. 24 Ten trials with MPFF out of forty using flavonoids were included. 24 The meta-analysis suggests that oral venoactive drugs considered as a whole reduce lower leg oedema (risk ratio (RR) 0.70, 95% confidence interval (CI) 0.63 to 0.78) and ankle circumference (mean difference −4.27 mm, 95% CI −5.61 to −2.93 mm) compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Cochrane review and meta-analysis of phlebotonics for venous insufficiency, published in 2020, analyzed 56 randomized, double-blind, placebo-controlled trials involving 7690 participants. 24 Ten trials with MPFF out of forty using flavonoids were included. 24 The meta-analysis suggests that oral venoactive drugs considered as a whole reduce lower leg oedema (risk ratio (RR) 0.70, 95% confidence interval (CI) 0.63 to 0.78) and ankle circumference (mean difference −4.27 mm, 95% CI −5.61 to −2.93 mm) compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…24 Ten trials with MPFF out of forty using flavonoids were included. 24 The meta-analysis suggests that oral venoactive drugs considered as a whole reduce lower leg oedema (risk ratio (RR) 0.70, 95% confidence interval (CI) 0.63 to 0.78) and ankle circumference (mean difference −4.27 mm, 95% CI −5.61 to −2.93 mm) compared with placebo. Little or no effect was evidenced for ulcer healing (RR 0.94, 95% CI 0.79 to 1.13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, particularly when dealing with larger samples, detection of low p -values may not indicate a clinically sensitive effect that leads to changes to medical paradigms. In an important systematic review conducted by Martinez-Zapata et al 27 on the subject of phlebotonics for venous insufficiency, it was suggested that phlebotonics are superior, on the basis of their statistical significance (p < 0.05), but the effect size observed was the result of a mean reduction of just 4.27 mm (95%CI 2.93–5.61 mm) in ankle circumference in 2,010 participants (15 studies), which, although true, does not indicate an evident benefit for patients with edema of the lower limbs.…”
mentioning
confidence: 99%
“…Por outro lado, especialmente, em amostragens mais vultosas, o encontro de p-valores reduzidos pode não representar em um efeito clinicamente sensível que leve à mudança de paradigmas médicos. Na importante revisão sistemática de Martinez-Zapata et al 27 sobre ventonônicos em insuficiência venosa, foi sugerida a superioridade de drogas venotônicas devido a sua significância estatística (p < 0,05), porém, a dimensão do efeito encontrada resultou em uma redução média de apenas 4,27 mm (IC95% 2,93–5,61 mm) na circunferência do tornozelo de 2.010 participantes (15 estudos), o que, apesar de verdadeiro, não representa um benefício evidente para o paciente com edema dos membros inferiores.…”
unclassified